Identification of Dominant Factors Affecting Study Time and Waiting Time of Mathematics Undergraduate Using the Least Absolute Shrinkage And Selection Operator (LASSO) - Hendra Cipta; Rina Widyasari; Linna Syahputri (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Higher education is a level of education that is able to produce and prepare graduates so that college graduates are able to compete and are ready to face the world of work. The aim of this research is to determine the dominant factors that influence the study period and waiting time for undergraduates in Department of Mathmatics FST UIN Sumatera Utara Medan until they get their first job in less than 9 months. The Least Absolute Shrinkage And Selection Operator (LASSO) method was used in this research, where this method is expected to be able to provide high accuracy results in terms of determining the most dominant factors. From the results of calculations using the LASSO method, the three most dominant factors that greatly influence the study period and waiting time for undergraduates are working status (X3), organizational participation (X5), grade point average (X2), final assignment position (X2). By producing this most dominant factor, it is hoped that mathematics study programs will care more about their students by making major and minor improvements to future accreditation